ANALISIS YURIDIS PELANGGARAN DISIPLIN TERHADAP ANGGOTA POLRI DALAM UPAYA MENINGKATKAN KUALITAS PENEGAK HUKUM DI INDONESIA (STUDI PENELITIAN PADA POLDA KEPRI) - Muhammad Fadli; Idham Idham; Christiani Prasetya Sari (Ensiklopedia of Journal, 2022)
The construction of the topic of the journal above is: "Juridical Analysis of Discipline Violations Against Police Members in an Effort to Improve the Quality of Law Enforcement in Indonesia", with the formulation of the problem: How are the Legal Arrangements, Implementation, Constraint Factors and Solutions to Discipline Violations Against Police Members in Efforts Improving the Quality of Law Enforcement in Indonesia? The type of writing is normative law, using legal research methodology, supported by secondary data, and using a qualitative approach, and to obtain secondary data, obtained through library research. For the grand theory, Jeremy uses the theory of happiness law (utilitarianism) by Jeremy Bentham, middle theory uses the legal theory of substance of law by M.friedman and applied theory uses the theory of responsibility law by Philip Nonet and Philip Selznick. The results of the analysis concluded, As part of the process of administering the state, the Police institution is also bound to certain legal rules and procedures, and is controlled and accountable to the law.Keywords: Discipline Violation, Law Enforcement, the rule of law.